Synthesis of new metronidazole derivatives with suspected antimicrobial activity - Yasser F. Mustafa; Karam A. Al - dabbagh; Manal F. Mohammed (University of Mosul, 2008)
Metronidazole has a bactericidal effect against many anaerobic gram positive and gram negative bacteria, but has no activity against aerobic bacteria. Metronidazole activity is mostly contributed to its reduced form that produced from anaerobic reduction inside the micro-organisms. In this research, the reduced form of metronidazole was synthesized and termed compound ( I ) which diazonated to form a diazonium interme-diate, this intermediate coupled with two phenolic compounds to give compounds ( II ) and ( III ) which are azo derivatives. The structures of these compounds were identified by physical and spectroscopic ( U.V. and FTIR ) techniques. The antibacterial activity of the synthesized compounds were examined against two aerobic gram positive bacteria ( Staphylococcus aureus, Streptococcus pneumoniae ); two aerobic gram negative bacteria (Pseudomonas aeruginosa, Escherichia coli ) and one anaerobic gram positive bacteria ( Clostridium Perfringens ) by using two techniques: dilution and disc diffusion methods. Opposite to our expectance, these products showed no antibacterial activity against the tested bacteria at the concentrations used